Acute toxicity in patients treated with concurrent chemoradiotherapy with proton versus intensity‐modulated radiation therapy for nonmetastatic head and neck cancers. Issue 11 (13th July 2022) - Kim, Kristine N.; Harton, Joanna; Mitra, Nandita; Lukens, John N.; Lin, Alexander; Amaniera, Isabella; Doucette, Abigail; Gabriel, Peter; Baumann, Brian; Metz, James; Wojcieszynski, Andrzej
Abstract: Background: We evaluated if proton therapy is associated with decreased acute toxicities compared to intensity‐modulated radiation therapy (IMRT) in patients receiving concurrent chemoradiotherapy for head and neck cancers. Methods: We analyzed 580 patients with nonmetastatic head and neck cancers. Primary endpoint was any 90‐day grade ≥3 toxicity, prospectively collected and graded per CTCAEv4. Modified Poisson regression models were used. Results: Ninety‐five patients received proton and 485 IMRT. The proton group had more HPV‐positive tumors (65.6 vs. 58.0%, p = 0.049), postoperative treatment (76.8 vs. 62.1%, p = 0.008), unilateral neck treatment (18.9 vs. 6.6%, p < 0.001) and significantly lower doses to organs‐at‐risk compared to IMRT group. Adjusted for patient and treatment characteristics, the proton group had decreased grade 2 dysgeusia (RR0.67, 95%CI 0.53–0.84, p = 0.004) and a trend toward lower grade ≥3 toxicities (RR0.60, 95%CI 0.41–0.88, p = 0.06). Conclusions: Proton therapy was associated with significantly reduced grade 2 dysgeusia and nonstatistically significant decrease in acute grade ≥3 toxicities compared to IMRT.